Exploring Vibration Analysis in Open Impeller Centrifugal Pumps: A Comparative Study between Simulation Modeling and Experimental Measurements - Wilson Janoyan; Wang Hansen (Jurnal Mekintek : Jurnal Mekanikal, Energi, Industri, Dan Teknologi, 2023)
This research investigates open impeller centrifugal pump vibration analysis through a comprehensive examination of simulated predictions and empirical measurements. The study aims to assess the correlation between simulated models and experimental data, exploring the sensitivity of pump vibrations to operational parameters and elucidating the strengths and limitations of both approaches. Utilizing a validated simulation model, the research closely compares predicted vibration characteristics with empirical measurements obtained from controlled experiments. The analysis reveals a strong correlation between simulated and measured data, validating the simulation's predictive accuracy in replicating the pump's vibration behavior. Despite minor discrepancies, primarily at higher operational speeds, the overall alignment reaffirms the simulation's credibility. The study highlights the pump's sensitivity to operational parameters, emphasizing the influence of flow rates, material properties, and rotational speeds on vibration levels. This sensitivity underscores the significance of meticulous parameter optimization for mitigating vibrations and enhancing pump efficiency. While simulations excel in predictive capabilities, experiments provide validation and realism, yet both possess inherent constraints. This research underscores the implications for engineering advancements, predictive maintenance strategies, and identifies avenues for further research. Leveraging the validated simulation model offers prospects for tailored designs, proactive maintenance interventions, and enhanced operational safety in industrial settings reliant on pump systems.